2011
DOI: 10.5606/kbbihtisas.2011.036
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the clinical effects of isotretinoin on chronic rhinosinusitis

Abstract: Objectives: This study aims to evaluate the clinical effects of isotretinoin (13-cis-retinoic acid), a derivative of retinoic acid, on the clinical features of chronic rhinosinusitis. Patients and Methods:The study group included 25 chronic rhinosinusitis patients (16 females, 9 males; mean age 25.2±6.8 years; range 15 to 25 years) who were on isotretinoin for acne treatment, while the control group consisted of 25 chronic rhinosinusitis patients (15 females, 10 males; mean age 25.2±6.8 years; range 15 to 25 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…25 A study of 25 Turkish patients with and 25 without chronic rhinosinusitis found that isotretinoin resulted in long-term improvement in symptoms and computed tomography score and fewer acute flares. 26 Together, these studies suggest a potential role of P. acnes in the pathogenesis of sinopulmonary disease. However, it is possible that the improvement was related to the innate anti-inflammatory properties of isotretinoin.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…25 A study of 25 Turkish patients with and 25 without chronic rhinosinusitis found that isotretinoin resulted in long-term improvement in symptoms and computed tomography score and fewer acute flares. 26 Together, these studies suggest a potential role of P. acnes in the pathogenesis of sinopulmonary disease. However, it is possible that the improvement was related to the innate anti-inflammatory properties of isotretinoin.…”
Section: Discussionmentioning
confidence: 89%
“…A previous bacteriological study of 48 patients with chronic maxillary sinusitis found colonization of the sinuses with P. acnes and other anaerobes, and proposed that these bacteria may play a role in the pathogenesis of sinusitis . A study of 25 Turkish patients with and 25 without chronic rhinosinusitis found that isotretinoin resulted in long‐term improvement in symptoms and computed tomography score and fewer acute flares . Together, these studies suggest a potential role of P. acnes in the pathogenesis of sinopulmonary disease.…”
Section: Discussionmentioning
confidence: 91%
“…2 The reason of this is that in literature, the nasal dryness is considered to be the underlying mechanism causing the decreased MCT (which is the objective finding of isotretinoin use) and epistaxis (which is the subjective finding of isotretinoin use). 2,9,10,13,14 In our study, epistaxis was evaluated with ESS questionnaire. 15 Five (4.9%) patients had a history of epistaxis in the last 6 months before the treatment, and this number increased to 60 (59.4%) when the treatment was completed (P ¼ .021).…”
Section: Discussionmentioning
confidence: 99%
“…2 The reason of this is that in literature, the nasal dryness is considered to be the underlying mechanism causing the decreased MCT (which is the objective finding of isotretinoin use) and epistaxis (which is the subjective finding of isotretinoin use). 2,9,10,13,14…”
Section: Discussionmentioning
confidence: 99%